Academic And Licensure Examination Performances Of Accountancy Graduates Of A State University In The Philippines (Journal of Namibian Studies : History Politics Culture, 2024)
Certified Public Accountant Licensure Examination (CPALE) is considered to be one of the most difficult licensure examinations according to Dr. John S. Bala in 2008. A national downward trend in the CPALE performance can be observed in the published national passing rates by the Professional Regulation Commission (PRC) since May 2016 with 42.84% down to 14.32% in October 2019, which is the lowest in history. This led to this study which aimed to assess both the academic and CPALE performances of the accountancy graduates of the State University and to determine the relationship between the two performances. Using the descriptive method of research, the assessment of the 189 examiners who took the CPALE for the first time from May 2017 to October 2019 revealed that in terms of academic performance, the graduates had Very Satisfactory performance in Financial Accounting and Reporting. However, the graduates had the least satisfactory performance in Taxation, and were also reflected in terms of the CPALE performance. Also, the academic performance showed direct and moderate to strong relationship with the CPALE performance. Thus, University must review the curriculum, syllabi, profile and performance of the accounting teachers, instructional materials, and retention policies of its Accountancy program.